Literature Study: Analysis of the Use of E-Module Based on Corn -Oriented Social Skill in Elementary Science Learning - Ayik Fena Emilda; M. Fadlillah (Universitas Muhammadiyah Enrekang, 2023)
Technological progress is something that we cannot avoid in today's life, basically technological progress will go according to the progress of science. Every innovation is created to provide positive benefits for human life. Humanizing humans is very important in social life. The purpose of this study was to find out how to use corn-based skill-based e-modules in elementary science learning. By using the research method of literature study. This technique can be used by reading various literary works related to the problem under study, this strategy is used to gather basic information and points of view in writing. The use of e-modules is said to be more effective, efficient and practical if you have to use printed modules with indicators of social care. The two types of learning modules have differences with reinforcement using the t test that has been carried out, where the sig obtained is smaller than 0.05, so there is a difference between the two. The use of e-modules by integrating social skills with local corn wisdom in elementary science learning can maintain traditional knowledge and cultural empathy by understanding the perspectives and values ​​attached to the importance of corn in the lives of people in the surrounding environment.